Peningkatan Hasil Belajar Biologi Peserta Didik Melalui Penerapan Model Pembelajaran Kooperatif Tipe Group Investigation - Hironimus Pati; Yeskiel Nenokatu; Soli Arianti Hayon; Refli Aleksi Pello; Lensyana Patty; Yusmi Marice Taloen; Syarfiah (Program Studi Pendidikan Biologi Universitas Katolik Widya Mandira, 2024)
This study aims to improve students' biology learning outcomes through the implementation of the cooperative learning model Group Investigation (GI). This research is a classroom action research (CAR) conducted in two cycles. Each cycle included the stages of planning, action, observation, and reflection. The subjects of the study were 24 students of class X1 at SMA Negeri Keberbakatan Olahraga Flobamorata Kupang. Data were collected using a learning outcome test and analyzed descriptively and quantitatively. The results showed a significant improvement in students' learning outcomes. In cycle I, the average student score was 60.77, with a mastery level of 25%. In cycle II, the average score increased to 71.12, with a mastery level reaching 100%. This improvement was attributed to the systematic implementation of GI steps, including intensive guidance, the selection of relevant topics, and the use of supportive learning media. The GI learning model was not only effective in enhancing learning outcomes but also fostered collaboration and critical thinking skills among students.